The alpha-7 nicotinic acetylcholine receptor is involved in a direct inhibitory effect of nicotine on GnRH release: In vitro studies. (15th January 2018) - Messi, Elio; Pimpinelli, Federica; Andrè, Valentina; Rigobello, Chiara; Gotti, Cecilia; Maggi, Roberto
Abstract: The activation of nicotinic cholinergic receptors (nAChR) inhibits the reproductive axis; however, it is not clear whether nicotine may directly modulate the release of hypothalamic gonadotropin-releasing hormone (GnRH). Experiments carried out in GT1-1 immortalized GnRH neurons reveal the presence of a single class of high affinity α4β2 and α7 nAchR subtypes. The exposure of GT1-1 cells to nicotine does not modify the basal accumulation of GnRH. However, nicotine was found to modify GnRH pulsatility in perifusion experiments and inhibits, the release of GnRH induced by prostaglandin E1 or by K + -induced cell depolarization; these effects were reversed by D-tubocurarine and α-bungarotoxin. In conclusion, the results reported here indicate that: functional nAChRs are present on GT1-1 cells, the activation of the α-bungarotoxin-sensitive subclass (α7) produces an inhibitory effect on the release of GnRH and that the direct action of nicotine on GnRH neurons may be involved in reducing fertility of smokers. Highlights: Immortalized GnRH neurons (GT1-1) express acetylcholine nicotinic receptors. Nicotine has not effect on basal accumulation of GnRH. Nicotine affects the pulsatility of GnRH release from GT1-1 cells. Nicotine exerts an inhibitory action on stimulated GnRH release. The effect of nicotine does not affect intracellular cAMP levels.